EKLOGIT TERUBAH DAN BATUAN ASOSIASINYA SEBAGAI INDIKATOR SUBDUKSI PURBA SELAMA EOSEN ATAS HINGGA OLIGOSEN BAWAH DI SABUK METAMORFIK SULAWESI TENGAH BAGIAN TIMUR - INDONESIA - Syafri, Ildrem (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
Eclogite is a metamorphic of rock derived from the continental crust or oceanic crust that can provide important information about the early stages of the orogenic process. In the Sulawesi island, eclogite or eclogite facies known expose in several places (Tectonic Complex of Bantimala, Palu valley and Bongka River Valley). In addition to these locations, eclogite have been also decouvert in the melange complex of Wasuponda. Wasuponda Eclogites shows a different textural and mineralogical composition than Bantimala eclogite or eclogite facies of Palu valley on the response of different processes occured. These rocks formed in a different geological times which provides information about two ancient subduction zones in the western and eastern parts of Central Sulawesi metamorphic belt.This study aims to obtain meaningful information about the chronology of the Sulawesi island in the Cretaceous and post Cretacepous periods. Some selected examples of eclogite and its associated rocks have been observed in petrographic and rock forming minerals of these rocks have been analyzed chemically using Microprobe Camebax and SX 50. The results of chemical analysis allows us to classify minerals appropriately used in the pressure and temperature condition of the rock formation. The maximum pressure and temperature conditions obtained from the application of geotermobarometer is 21.6 kbar for a temperature in 580 °C, while the application Thermocalc program provides pressure with an average of 20.7 ± 2.6 kbar at temperature in 500 ± 29 ° C. The pressure and temperature are very similar to the P-T conditions of eclogite formation of complex tectonic of Bantimala. Taking into account the uncertainty of the values for pressure, then the pressure obtained indicate that the eclogite formation was in depth of 61 to 80 km.Altered eclogite from Wasuponda undergone retromorphose towards the amphibolite - and green schist facies, while in stability field of amphibolite facies, these rocks are associated with garnet quartz, rutile, phengit, epidote schist and garnet, hornblende, quartz, rutile, muscovite, epidote schist and they have emerged to the surface and presented as a component melange of Wasuponda. Pressure and temperature conditions obtained from the study indicates that the direction of the P-T path of Wasuponda eclogite is clockwise. This condition is contrary to the results obtained by Parkinson (1991) of the blue schist and rock associations derived from Melange Peleru.Eclogite from Wasuponda Melange Complex likely originated from the ancient oceanic crust and are classically referred to layer 3 which is expected a gabbroic by composition. Magmatic paragenesis on this rock observed under the microscope are: clinopyroxene, plagioclase and opaque minerals, while eclogitic paragenesis are garnet, omphasite, phengite and rutile. Mineral paragenesis indicating retromorphose stage are calco-sodic amphibole, sphene and plagioclase, and they are present in the matrix.When a rock undergones a retrograde stage (toward the surface), the eclogite experienced an oceanic metamorphism indicated by the presence of edenite, edenitic hornblende, also hematite, quartz and chlorite showing the amphibolitation process, while minerals like zoisite, albite, white mica, calcite and zeolite states sausuritisation process that occured at high temperature and low pressure.